Corporate Social Responsibility in the Digital Era: The Role of Emotions in Business Decision-Making and Operational Processes - Barile, Paolo; Bosco, Gerardo; D’Amore, Raffaele; Iandiorio, Guido (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Technological development in recent years – increasingly focused on computer science – has seen innovative solutions based on Artificial Intelligence (AI) and the Internet of Things (IoT) pervade every aspect of human knowledge. In the economic sphere, the need to include digital technologies in business processes has led to a radical change in the way companies operate, introducing a whole range of tools that can redefine their decision-making and organizational models. From the perspective of sustainability – a central theme for today’s enterprises – the advent of digital would seem to have led to significant benefits, through the optimal use of resources and constant monitoring of production activities and operational processes. However, while environmental and economic sustainability seem to be favoured by the automation of processes, the sense of inclusiveness of the human resources involved in the enterprise is increasingly diminished due to a progressive ‘de-empowerment’ of stakeholders with respect to decision-making dynamics. Using the Viable Systems Approach (vSa), our paper sets out to analyse the criticalities introduced by digital technology with respect to Corporate Social Responsibility (CSR) and to investigate the role of emotions within decision-making and operational processes, highlighting how a human-centred approach is essential for the sustainable development of modern companies.